Personality Types in Arabic Comprehension: Literature Review - Maryam Nur Annisa; Sahrul Muhamad; Muslim; Wildana Wargadinata (PT. Berkah Smart Academica, 2024)
Understanding the relationship between psycholinguistics and personality types in the comprehension of the Arabic language can help improve the effectiveness of language learning. This research aims to explore this relationship by focusing on how psycholinguistic factors and personality traits affect Arabic language acquisition and comprehension. Psycholinguistics studies how language is produced, understood, and acquired by individuals, while personality types encompass consistent characteristics that influence behavior and preferences. The research employed a qualitative approach, using a literature review method to gather and critically analyze relevant sources. The analysis aimed to identify correlations between psycholinguistics and personality types in the context of Arabic language learning. In Arabic language comprehension, psycholinguistics and personality type have a significant role. This study shows that individual personality types can affect vocabulary management, syntactic processing and semantic interpretation in Arabic. The results of this study provide a deeper understanding of the complexity of the relationship between language and human cognitive processes. In the context of Arabic language learning, it is important for individuals to understand their own personality types, as this will help them find effective learning methods and understand Arabic better.